Analysis of Load Diversion Due to AAACS Cable Breaks in the Bandar Jaya Lampung Distribution System - M Khoirul Anam; Made Wartana; Irrine Budi Sulistiawati (Universitas Darul Ulum, 2025)
The electric power distribution system is the final component that is connected to consumers in the energy transmission chain. This distribution system is particularly vulnerable lightning strikes that can cause conductor cables to break. The 20 kV distribution network of the Rambutan Feeder, under Bandar Jaya ULP in Lampung, experienced a lightning strike that resulted in the disconnection of the AAACS cable, leading to a power outage in the service area. The geographical conditions of the Lampung region, which has a high isokeraunic level, contribute significantly to the likelihood of lightning-related disturbances. Based on real data, this study analyzes the impact of disturbances caused by lightning strikes on Feeder and proposes mitigation strategies to minimize the effects of resulting power outages. Analysis using ETAP shows that the recomendation to divert the load sypply to the arimbi feeder is able to maintain the bus voltage at a rating of 19,86 KV.